التعليم الاهلي الفرنسي بين التأييد والمعارضة 1830/1900 - ليلى معلول; قريشي عبلة; وسيلة كرشو (جامعة الوادي - University of Eloued, 2025)
"ملخص الدراسة تهدف هذه الدراسة الى تسليط الضوء على تعليم الأهلي الفرنسي بين التأييد والمعارضة بالجزائر بين 1900-1830م، وذلك من خلال تحليل مظاهر التأييد والمعارضة التي أحاطت بهذا النوع من التعليم، سواء من قبل السلطات الاستعمارية الفرنسية أو من طرف بعض الفاعلين الجزائريين ركزت الدراسة على فهم الأهداف التي سعت السلطات الفرنسية إلى تحقيقها من خلال دعم هذا التعليم، مثل نشر الثقافة الفرنسية وترسيخ الهيمنة الاستعمارية مقابل دوافع التأييد الجزائري التي تراوحت بين الاضطرار والفرص الاجتماعية، وكذلك مواقف الرافضين الذين اعتبروا التعليم الأهلي وسيلة لطمس الهوية الوطنية والدينية. اعتمدت الدراسة على المنهج التاريخي التحليلي، الذي يتيح فهم الظاهرة التعليمية ضمن سياقها الزمني والسياسي، من خلال جمع وتحليل الوثائق التاريخية والتقارير الرسمية والمصادر الثانوية ذات الصلة. كما تم توظيف المنهج النقدي المقارنة المواقف وتفسيرها في ضوء الخلفيات الفكرية والثقافية والاجتماعية. توصلت الدراسة إلى أن التعليم الأهلي الفرنسي لم يكن موحد الأهداف أو النتائج، بل كان مجالا للتجاذب بين رؤى استعمارية ترمي إلى السيطرة الثقافية، ومواقف جزائرية متباينة بين الرفض المطلق والتعامل البراغماتي. كما أبرزت الدراسة أن المعارضة الجزائرية خاصة من طرف النخب الدينية والثقافية لعبت دورا في الحفاظ على الهوية الوطنية، رغم محاولات الاختراق الثقافي والاستيعاب الفرنسي." "Summary This study aims to shed light on the education of French citizens between support and opposition in Algeria between 1830 and 1900, by analyzing the manifestations of support and opposition that surrounded this type of education, whether by the French colonial authorities or by some Algerian actors. The study focused on understanding the goals that the French authorities sought to achieve by supporting this education, such as the dissemination of French culture and the consolidation of colonial domination, as opposed to the motives of Algerian support, which ranged from coercion and social opportunities, as well as the positions of rejectionists who considered public education a way to blur national and religious identity. The study was based on the historical-analytical approach, which makes it possible to understand the educational phenomenon within its chronological and political context, through the collection and analysis of historical documents, official reports and relevant secondary sources. The critical approach was also employed to compare and interpret situations in the light of intellectual, cultural and social backgrounds. The study found that French public education did not have uniform goals or results, but was an area of attraction between colonial visions aimed at cultural domination, and different Algerian attitudes between absolute rejection and pragmatic dealing. The study also highlighted that the Algerian opposition, especially from the religious and cultural elites, played a role in preserving the national identity, despite attempts at cultural penetration and French assimilation."
مذكرة ماستر قسم التاريخ تخصص المغرب العربي المعاصر
Keywords: التعليم; المعارضة; التأييد; الاستعمار الفرنسي; التعليم الأهلي; الجزائر; Algeria; public education-; French colonization